Classroom Incivility Going Viral on Social Media: One Professor’s Encounters - Anuik, Jonathan (Journal of Contemporary Issues in Education, 2024)
The advent of social media expands the domain of the standard classroom. The outcome is that incidents of conflict, also known as classroom incivility, exist not only within the conventional classroom. They can take place on social media platforms. In this paper, the author draws on his experience with a complaint about an assignment in one of his classes that surfaced on X (formerly Twitter), feedback on the assignment that took the shape of a story on Instagram, and his response to the activity in the two venues. He draws on the concept of classroom incivility and reflects on how this term, named to describe conflict in in-person classrooms, is relevant on social media platforms.